Population Genetics : A Review - Bedge, Kiran; Pratima Salunkhe, (International Journal of Scientific Research in Science and Technology, 2024)
Genetics is the study of genes and genetic variations alongwith the hereditary characteristics of an organism. Genetics is a central pillar of biology. It overlaps with other areas, such as: Agriculture, Medicine, Biotechnology. Genetics involves studying:Gene structure and functionGene variation and changesHow genes affect health, appearance, and personality.Population genetics studies genetic variation within and among populations, based on the Hardy-Weinberg law, which remains constant in large populations with random mating and minimal mutation, selection, and migration.
Keywords: Genetics; Genes; Population; Roadmap; Epigenetics; Biochemical; Hardy-Weinberg Equilibrium; Myocardial Infraction